The Dynamics of Social Solidarity in Local Traditions: An Ethnographic Analysis of Kaboro Co'i in Wora Village, Bima Regency - Arhan Arhan (Tabéq: Journal of Local Wisdom, Belief, and Peace, 2026)
This research examines the values of social solidarity embedded in the Kaboro Co'i tradition in Wora Village, Bima Regency, within the context of ongoing modernization. Utilizing an ethnographic qualitative methodology, data were gathered through participatory observation, in-depth interviews with traditional leaders, community figures, and local practitioners, as well as supporting documentation. Data analysis employed the Miles and Huberman interactive model, which includes data collection, reduction, display, and conclusion drawing. The results indicate that the financial contribution recording system in Kaboro Co'i does not operate as a formal debt-credit mechanism; instead, it serves as a system of social memory and an ethical bond that sustains long-term relationships among residents. The tradition embodies key social solidarity values such as empathy, trust-based reciprocity, familial togetherness, and mutual cooperation (gotong royong). These aspects demonstrate a transformation of mechanical solidarity that adapts to contemporary socioeconomic pressures. In conclusion, Kaboro Co'i functions as an adaptive cultural strategy that maintains social cohesion and economic resilience, providing a counterbalance to the individualistic tendencies associated with modern life in the Wora Village community.